2010
DOI: 10.1111/j.1468-2427.2010.00959.x
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Policies in Bulgaria: European Integration, Postsocialist Dynamics and Local Level Initiatives

Abstract: This article investigates public policies aimed at developing industrial clusters in Bulgaria by looking at initiatives at supranational, national and local levels. It argues that cluster policies have functioned as paths directing actions in the postsocialist transformation of Bulgaria. In doing so, it seeks answers to the following research questions: what are the connections between policy implementation, institutional changes and economic transformation at the national and local levels in Bulgaria; what is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The theoretical section of this paper links Beck and Grande's approach with much of the literature in political geography, which shows the rescaling of European political authority at all levels (Johnson, 2008;Mamadouh and Van der Wusten, 2008;Murphy, 2008), and in the political sciences, which describes Europeanization as the outcome of the dynamic relation between EU-level and nationlevel administrations (Green Cowles et al, 2001;Knill, 2001;Olsen, 2002Olsen, , 2007Schimmelfennig and Sedelmeier, 2005;Graziano and Vink, 2007). In particular, it links Beck and Grande's argument on the contradictory character of Europeanization with geographers' findings concerning the design and implementation of specific EU policies (Kostadinova 2009;Sellar et al, 2011).…”
Section: Introductionmentioning
confidence: 88%
“…The theoretical section of this paper links Beck and Grande's approach with much of the literature in political geography, which shows the rescaling of European political authority at all levels (Johnson, 2008;Mamadouh and Van der Wusten, 2008;Murphy, 2008), and in the political sciences, which describes Europeanization as the outcome of the dynamic relation between EU-level and nationlevel administrations (Green Cowles et al, 2001;Knill, 2001;Olsen, 2002Olsen, , 2007Schimmelfennig and Sedelmeier, 2005;Graziano and Vink, 2007). In particular, it links Beck and Grande's argument on the contradictory character of Europeanization with geographers' findings concerning the design and implementation of specific EU policies (Kostadinova 2009;Sellar et al, 2011).…”
Section: Introductionmentioning
confidence: 88%
“…Ian Drahokoupil (: 3) demonstrated that an internationally oriented service sector, composed of intellectuals, business consultants and policy analysts that he calls the ‘comprador service sector’, was instrumental in aligning domestic policies with the demands of international business. Others have demonstrated that the EU played a crucial role in the emergence of a new pan‐European service sector devoted to the management of EU and other grants (Lovering, ; Sellar et al ., ). This section analyzes the Italian IPC as a conjunction between comprador and grant‐managing service sectors, and as a carrier of ideological change.…”
Section: Supporting Italian Investments In the Slovak State: An Instimentioning
confidence: 97%
“…On the one hand, the agglomeration results from profit maximization and thus increases the economic efficiency and competitiveness of the industry. Policies may benefit from foreign investment and economic reconstruction responding to the agglomeration dynamics [65,66]. On the other hand, policies might have played an influential role during the agglomeration process.…”
Section: Discussionmentioning
confidence: 99%